Influence of Teachers' Deep Knowledge about Fractions on the Students' Learning in 4th grade - Palmenia de la Cruz Rodríguez Rojas; Carlos Arturo Navarrete Rojas (Universidad Autónoma de Baja California, 2020)
The aim of this study is to establish to what extent the teacher's deep knowledge about fractions and knowledge for the teaching of fractions, adjusted by the socioeconomic level and the school mathematical knowledge (SIMCE), influences the learning of the students in the conceptualization of fractions in fourth grade. Information was obtained from 378 4th grade students of 9 schools and their respective mathematics teachers. The results of the regression analysis show that effect of teacher's deep knowledge is significant in the learning per student (p = 0.001), beyond what is explained by the SIMCE score of the school, which is also significant (p = 0.02).